Long-read genome sequencing provides novel insights into the harmful algal bloom species Prymnesium parvum - Jianbo Jian; Zhangyan Wu; Arisbe Silva-Núnez; Xiaohui Li; Xiaomin Zheng; Bei Luo; Yun Liu; Xiaodong Fang; Christopher T. Workman; Thomas Ostenfeld Larsen; Per Juel Hansen; Eva C. Sonnenschein (Science of The Total Environment, 2025)

Corrigendum to “long-read genome sequencing provides novel insights into the harmful algal bloom species Prymnesium parvum” [science of the total environment, 908 (2024)/ 168,042] - Jianbo Jian; Zhangyan Wu; Arisbe Silva-Núñez; Xiaohui Li; Xiaomin Zheng; Bei Luo; Yun Liu; Xiaodong Fang; Christopher T. Workman; Thomas Ostenfeld Larsen; Per Juel Hansen; Eva C. Sonnenschein (Science of The Total Environment, 2025)

Prenatal exposure to polycyclic aromatic hydrocarbons and executive functions at school age: Results from a combined cohort study - Yu Ni; Adam A. Szpiro; Christine T. Loftus; Tomomi Workman; Alexis Sullivan; Erin R. Wallace; Anne M. Riederer; Drew B. Day; Laura E. Murphy; Ruby H.N. Nguyen; Sheela Sathyanarayana; Emily S. Barrett; et al. (International Journal of Hygiene and Environmental Health, 2024)

Long-read genome sequencing provides novel insights into the harmful algal bloom species Prymnesium parvum - Jianbo Jian; Zhangyan Wu; Arisbe Silva-Núñez; Xiaohui Li; Xiaomin Zheng; Bei Luo; Yun Liu; Xiaodong Fang; Christopher T. Workman; Thomas Ostenfeld Larsen; Per Juel Hansen; Eva C. Sonnenschein (Science of The Total Environment, 2024)

Early adaptive developments of Pseudomonas aeruginosa after the transition from life in the environment to persistent colonization in the airways of human cystic fibrosis hosts - Martin Holm Rau; Susse Kirkelund Hansen; Helle Krogh Johansen; Line Elnif Thomsen; Christopher T. Workman; Kristian Fog Nielsen; Lars Jelsbak; Niels Høiby; Lei Yang; Søren Molin (Environmental Microbiology, 2010)
Summary Pseudomonas aeruginosa is an opportunistic pathogen ubiquitous to the natural environment but with the capability of moving to the host environment. Long‐term infection of the airways of cystic fibrosis patients is associated with extensive genetic adaptation of P. aeruginosa , and we have studied cases of the initial stages of infection in order to characterize the early adaptive processes in the colonizing bacteria. A combination of global gene expression analysis and phenotypic characterization of longitudinal isolates from cystic fibrosis patients revealed well‐known characteristics such as conversion to a mucoid phenotype by mucA mutation and increased antibiotic resistance by nfxB mutation. Additionally, upregulation of the atu operon leading to enhanced growth on leucine provides a possible example of metabolic optimization. A detailed investigation of the mucoid phenotype uncovered profound pleiotropic effects on gene expression including reduction of virulence factors and the Rhl quorum sensing system. Accordingly, mucoid isolates displayed a general reduction of virulence in the Caenorhabditis elegans infection model, altogether suggesting that the adaptive success of the mucoid variant extends beyond the benefits of alginate overproduction. In the overall perspective the global phenotype of the adapted variants appears to place them on paths in direction of fully adapted strains residing in long‐term chronically infected patients.